Food Price Volatility and Its Implications for Food Security and Policy - Kalkuhl, Matthias; von Braun, Joachim; Torero, Maximo; Kalkuhl, Matthias; von Braun, Joachim; Torero, Maximo (Cham Springer Nature, 2016)
Agricultural Economics
English
Keywords: Development economics & emerging economies; Technology, engineering, agriculture; Agricultural Economics